Tramontane Whispers or Immanent Voices: The Religious Analysis of Secularization in Nicolás Gómez Dávila (2023)
An authentic political theology, a religious analysis of politics, is manifested in the works of Gómez Dávila. This article examines the theological sources of modern thought from the perspective of Gómez Dávila, to understand secularization as a distinctive political phenomenon of modernity. First, we must explain the significance of the 13th century as a period of ruptures in the Catholic worldview influenced by Averroes. Furthermore, it demonstrates how Averroist ideas find resonance within Pascal and Romanticism, thereby positioning Gómez Dávila within the Averroist debate. Finally, a conclusion is presented with the main point being that, for Gómez Dávila, only a medieval mystic and fideist is truly reactionary since the modern conception of politics underlies the Thomistic dialogue between faith and reason.